Description of Alocobisium tibetense sp. nov., representing the first record of the pseudoscorpion family Syarinidae (Arachnida: Pseudoscorpiones) from China - Hu, Junfang; Zhang, Feng (Zootaxa, 2013)
Alocobisium tibetense sp. nov. is described from Xizang Autonomous Region, representing the first record of Syarinidae from China. Alocobisium rahmi Beier, 1976 is re-described from type material and a key is given to the genus.